Investigation of exhaust emissions and performance of a diesel engine fueled with preheated raw grape seed oil/propanol blends - Hazar, Hanbey; Sevinc, Huseyin (Elsevier Science Sa, 2023)
The enrichment of alternative fuels with oxygen in diesel engines is one of the influential techniques utilized to improve performance and lower emissions. This work analyzed the influences of grape seed oil-propanol fuel mixture, which can be an alternative to diesel fuel, on diesel engine. Grape seed oil (GSO), which was used raw, was extracted from grape seeds by cold pressing method. In order to improve physical and chemical attributes of fuel mixtures, preheating process was applied. The engine tests were realized in an air cooled single cylinder diesel engine. GSO was stirred with diesel fuel in volumes of 10% and 30% and also 5% propanol was added. In this study, CO, NOX, smoke, HC, BSFC, EGT, BTE, vibration and noise parameters of diesel engine were taken into consideration. Moreover, thermal images of the engine were also recorded. The results indicated that BSFC, CO, smoke and HC diminished but NOX, BTE, EGT, vibration and noise increased in the preheated and propanol added test fuels. Preheating process for grape seed oil ensured a convenient fuel flow and decreased the oil viscosity and propanol addition contributed to the enrichment of the fuel in terms of oxygen.
Keywords: Grape seed oil; Propanol; Preheating; Diesel engine; Exhaust emissions; Performance